The impact of sentinel node dissection on disease‐free and overall tumour‐specific survival in melanoma patients: a single centre group‐matched analysis of 1192 patients. (29th September 2016) - Geimer, T.; Sattler, E.C.; Flaig, M.J.; Ruzicka, T.; Berking, C.; Schmid‐Wendtner, M.H.; Kunte, C.
Abstract: Background: Sentinel lymph node dissection (SLND) is considered a standard staging procedure providing important prognostic information on melanoma patients. It remains a matter of debate, whether SLND and hence, removal of potential lymph node micrometastasis will alter survival outcome. Objective: The aim of this group‐matched analysis was to compare survival data of a large cohort of melanoma patients who were treated by wide local excision only (WLE) and nodal observation (WLE group) to a group of patients treated with WLE plus SLND group to investigate the potential therapeutic benefit of SLND in the treatment of patients with melanoma. Methods and materials: A total of 596 consecutive patients who had undergone WLE plus SLND between 1996 and 2003 were assessed. As a historical control group 596 patients treated with WLE and nodal observation but without SLND between 1986 and 1995 were selected. The groups were matched according to sex, age, Breslow tumour thickness and localization of primary tumour. The adjuvant treatment and follow‐up examinations were performed according to protocols of the German Dermatologic Cooperative Oncology Group (DeCOG) and applicable study protocols that our clinic participated in; and hence, subject to change over time. Results: Kaplan–Meier testing revealed significant differences in survival in favour of the SLND group. Mean overall tumour‐specific survival (OS) was 102.7 months in the SLND group vs. 97.0 months in the WLE group respectively ( P ‐value: 0.024). Disease‐free survival (log–rank test: 0.003) and time to lymph node progression ( P ‐value: <0.01) also differed significantly between the two groups. Conclusion: SLND is not only an important diagnostic procedure, but might also be of therapeutic benefit in terms of disease‐free and overall tumour‐specific survival of melanoma patients.